2018
DOI: 10.12659/ajcr.910725
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea in Pregnancy: A Case Report of a Third Trimester Mediastinal Mass in Pregnancy

Abstract: Patient: Female, 34Final Diagnosis: Primary mediastinal b cell lymphomaSymptoms: Cough • shortness of breathMedication: —Clinical Procedure: Cesarean deliverySpecialty: Obstetrics and GynecologyObjective:Rare co-existance of disease or pathologyBackground:Dyspnea in pregnancy is common and attributable to a variety of etiologies including normal physiology. The obstetric provider is challenged with distinguishing between physiologic versus pathologic dyspnea.Case Report:A 31-year-old G2 P1001 female at 34 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…Approximately half of women without a history of cardiorespiratory disease reported dyspnea before the 19 th week of pregnancy, and 76% by the 31st week. [11][12][13][14]16 However, our study found similar results because many women complained of dyspnea. Number of pregnant women was 95(29.4%) in 1 st trimester, 112(34.6%) from 2 nd trimester and 116(35.9%) from 3 rd trimester.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Approximately half of women without a history of cardiorespiratory disease reported dyspnea before the 19 th week of pregnancy, and 76% by the 31st week. [11][12][13][14]16 However, our study found similar results because many women complained of dyspnea. Number of pregnant women was 95(29.4%) in 1 st trimester, 112(34.6%) from 2 nd trimester and 116(35.9%) from 3 rd trimester.…”
Section: Discussionsupporting
confidence: 68%
“…In terms of haemoglobin levels, our study found no statistically significant difference between the study and control groups (p=0.508). 16,17 Our study population showed another similarity regarding hemoglobin (10.93±1.2) and it was found statistically insignificant (p=0.272).…”
Section: Ii)mentioning
confidence: 54%
“… 23 There are only a few studies on the association between changes in cardiac parameters and dyspnea in pregnancy, and our results are consistent with their findings. 2 - 18 …”
Section: Discussionmentioning
confidence: 99%
“…It is reported in 60% to 70% of normal pregnant women in the third trimester. 1 - 2 While dyspnea is insignificant and clinically negligible in some cases, it might be severe and debilitating in a cluster of patients. Only 3.2% of women experience severe dyspnea within their first 20 weeks of gestation, with the rate rising to about 37.5% in the third trimester.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil penelitian didapatkan wanita usia 31 tahun dengan G2 P1 A0 pada usia kehamilan 34 minggu mengalami dispnea, takikardi dan ketidakmampuan untuk berbabaring terlentang. Pencitraan menunjukan massa mediastinal anterior heterogen yang besar (14,8x11,5 cm) (Reeder et al, 2018). Selain gangguan pernafasan kehamilan secara fisiologis juga dapat menyebabkan perubahan pada sistem pernafasan dan kardiovaskuler yang disebabkan karena peningkatan kebutuhan metabolisme ibu dan janin.…”
Section: Metodeunclassified